Atherosclerotic cardiovascular disease risk stratification and management in type 2 diabetes: review of recent evidence-based guidelines - Gourdy, Pierre; Schiele, François; Halimi, Jean-Michel; Kownator, Serge; Hadjadj, Samy; Valensi, Paul (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of mortality and morbidity in individuals with type 2 diabetes mellitus (T2DM). Accordingly, several scientific societies have released clinical practice guidelines to assist health professionals in ASCVD risk management in patients with T2DM. However, some recommendations differ from each other, contributing to uncertainty about the optimal clinical management of patients with T2DM and established ASCVD or at high risk for ASCVD. Thus, the purpose of this paper is to discuss recent evidence-based guidelines on ASCVD risk stratification and prevention in patients with T2DM, in terms of disparities and similarities. To close the gap between different guidelines, a multidisciplinary approach involving general practitioners, endocrinologists, and cardiologists may enhance the coordination of diagnosis, therapy, and long-term follow-up of ASCVD in patients with T2DM.